Humans in Africa’s wet tropical forests 150 thousand years ago - Eslem Ben Arous; James A. Blinkhorn; Sarah Elliott; Christopher A. Kiahtipes; Charles D. N’zi; Mark D. Bateman; Mathieu Duval; Patrick Roberts; Robert Patalano; Alexander F. Blackwood; Khady Niang; Eugénie Affoua Kouamé; et al. (Nature, 2025)
Abstract Humans emerged across Africa shortly before 300 thousand years ago (ka)1–3. Although this pan-African evolutionary process implicates diverse environments in the human story, the role of tropical forests remains poorly understood. Here we report a clear association between late Middle Pleistocene material culture and a wet tropical forest in southern Côte d’Ivoire, a region of present-day rainforest. Twinned optically stimulated luminescence and electron spin resonance dating methods constrain the onset of human occupations at Bété I to around 150 ka, linking them with Homo sapiens. Plant wax biomarker, stable isotope, phytolith and pollen analyses of associated sediments all point to a wet forest environment. The results represent the oldest yet known clear association between humans and this habitat type. The secure attribution of stone tool assemblages with the wet forest environment demonstrates that Africa’s forests were not a major ecological barrier for H. sapiens as early as around 150 ka.